1991
DOI: 10.1097/00006123-199109000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Disc herniation in cervical fracture subluxation

Abstract: Previous reports of computed tomographic scan with contrast myelography in cervical spinal cord injury have shown a rate of disc herniation of less than 5%. We hypothesized that injuries associated with forces adequate to cause bone or ligamentous injury in the region of the disc space could be associated with higher and more significant rates of disc herniation. Thirty-seven consecutive traumatic midcervical fracture subluxations were reviewed. Fracture subluxation was defined by fracture of the facet joints,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The type of surgery, anterior or posterior, not only depends on the direction of instability and type of fracture, but is also influenced by spinal canal compromise with bone fragments, epidural hematoma or herniated disc material. Traumatically herniated disc material causing medullary compression [7,14], either before or after reduction, is a probable confounding factor in a retrospective study setting of this kind. Most of the cases in this series were treated before the era of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The type of surgery, anterior or posterior, not only depends on the direction of instability and type of fracture, but is also influenced by spinal canal compromise with bone fragments, epidural hematoma or herniated disc material. Traumatically herniated disc material causing medullary compression [7,14], either before or after reduction, is a probable confounding factor in a retrospective study setting of this kind. Most of the cases in this series were treated before the era of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Even though computed tomography (CT) myelography was still the principal neuroimaging study before MRI, the reported prevalence of disc herniation with cervical spine injuries was \5% [3,7]. However, with the use of MRI, the reported incidence of traumatic disc herniation increased to about 40% [11,12,24].…”
Section: Discussionmentioning
confidence: 99%
“…Disc extrusion can occur because these injuries may cause the rupture of the posterior longitudinal ligament and posterior annulus. Previous reports have suggested that up to 40% of all fracture-dislocations of the cervical spine are associated with intervertebral disc herniation [12,22,24]. Traumatic cervical disc herniation is thought to cause further compression of the spinal cord and increase the risk of neurological deterioration during closed or open reduction [10,20,25].…”
Section: Introductionmentioning
confidence: 99%
“…Harrington et al (1991) have shown that cervical disc herniations are common in patients with cervical fracture subluxations. In their series of 37 consecutive patients with cervical fracture subluxation, disc hemiation was demonstrated at the level of the injury in one third of the cases.…”
Section: Discussionmentioning
confidence: 99%